Balbiani body formation and cytoplasmic zonation during early oocyte development in two Clupeiform fishes. Issue 5 (16th March 2022) - Charitonidou, Katerina; Panteris, Emmanuel; Ganias, Kostas
Abstract: The Balbiani body (Bb) was examined in primary growth phase oocytes for the first time in two clupeoid fish species, the Mediterranean sardine, Sardina pilchardus, and the European anchovy, Engraulis encrasicolus, which belong to different families, Clupeidae and Engraulidae, respectively. Cytoplasmic morphological changes of early secondary growth oocytes were also investigated using confocal laser scanning microscopy, light and transmission electron microscopy. The ultrastructural observations showed that the two species develop a distinct spherical Bb. However, differences in the cytoplasm, mainly in the perinuclear area, were observed. Briefly, in sardine the Bb coexists with a thick perinuclear ring containing mitochondria, nuage, endoplasmic reticulum and small vesicles, while in anchovy this perinuclear ring is thinner, consisting of complexes of nuage and mitochondria. After the disassembly of the Bb, a prominent cytoplasmic zonation develops in the secondary growth oocytes of sardine and anchovy, although with different organelle distribution between the two species. Sardine oocytes exhibit a thick zone of endoplasmic reticulum around the nucleus, whereas in those of anchovy, a thick mitochondria‐rich ring surrounding the nucleus was observed. The cytoplasmic characteristics, such as the perinuclear ring in primary oocytes in sardine and the mitochondria‐rich ring of early secondary oocytes in anchovy, are also discernible in histological sections by standard procedures and could thus be used as indicators of maturity or imminent spawning period in routine light microscopy observations, providing a valuable tool for applied fisheries biology.